(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to determine the influence of leadership and work motivation on the performance of village apparatus mediated by organizational commitment as a mediating variable in Ranah Batahan District, West Pasaman Regency. The method used in this study is to use multiple linear regression analysis and path analysis. The results of the research obtained based on the Partial Test (t-test) model 1 were obtained: (a) there was no positive and significant influence of leadership on organizational commitment, as evidenced by the t-calculated value for the leadership variable (X1) 1.642 < t-table 1.661. (b) There is a positive and significant influence of work motivation on organizational commitment, as evidenced by the t-calculated value of the work motivation variable (X2) 54,497 > t-table 1,661. The results of the research obtained based on the Partial Test (t-test) model 2 were obtained: (a) There is a significant influence of leadership on employee performance, as evidenced by the t-calculated value for the leadership variable (X1) 2.979 > t-table 1.661.(b) There is a significant influence of work motivation on employee performance as evidenced by the t-calculated value for the work motivation variable (X2) 2.478 > t-table 1.661. (c) There is a positive and significant influence of organizational commitment on employee performance, as evidenced by the t-calculated value for the organizational commitment variable (Z) 3.081 > t-table 1.661. Thus, the influence of leadership and work motivation on employee performance Mediated by organizational commitment as an intervening variable in Ranah Batahan District, West Pasaman Regency is feasible and correct. And based on the Determination coefficient (R2) test of model 1, the value is 0.490 or 49%, this shows that the percentage of contribution of independent variables of leadership and work motivation is 0.490 or 49%. While the remaining 51% was influenced by other variables outside this study. And based on the Determination coefficient (R2) test of model II, the value is 0.525 or 52.5%, this shows that the percentage of contributions of independent variables of leadership, work motivation and organizational commitment to employee performance is 0.525 or 52.5%, while the remaining 47.5 is influenced by other variables outside of this study.